Breastfeeding Practices and Parental Employment in Japan - Miki Kobayashi; Emiko Usui (Institute for the Study of Labor (IZA), 2014)
Much research shows that breastfeeding provides short- and long-term health benefits for both mothers and their children. However, few studies have yet investigated the factors which may promote or inhibit breastfeeding practices in Japan. To fill this research gap, this paper uses data newly gathered in 2012 on breastfeeding initiation and duration for each child of each mother, which enable us to estimate mother fixed-effects models that control for unobserved differences among mothers. Compared to mothers who leave their jobs after childbirth, mothers who return to work within a year after childbirth do not significantly differ in breastfeeding initiation but have a breastfeeding duration which is shorter by 1.654 months. On the other hand, when fathers work under a flextime system after childbirth, breastfeeding initiation is higher, and the duration is longer by 4.418 months. Therefore, letting fathers work under a flextime system would help promote breastfeeding practices in Japan.
Keywords: J13; 330; breastfeeding; maternal employment; paternal job responsibility; Japan